Pengkaryaan drama radio kepada anggota Bengkel Sastra FBS UNM sebagai media alternatif pelestarian cerita rakyat - Khaeruddin Khaeruddin; Prusdianto Prusdianto (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Folklore is a story that originates from thecommunity and develops in society in a descending way and itis delivered orally. The younger generation at this time hasbegun to be less interested in folklore because it is deemedirrelevant to the times of the modern era of globalization. Theydo not realize that there are many moral stories in folklore.Based on that problem, the community action program wasmade. The program title was “Creating Radio Drama by themembers of Literary Studio of FBS UNM